Public-Private Partnerships in Tanzania: Preliminary Observations on Performance - Moshi, Humphrey (Tanzania Journal for Population studies and Development, 2009)
The quest for New Public Management (NPM) reforms was informed by the need to enhance efficiency and reduce costs. This triggered the shift from traditional public administration to public management. This shift embraced not only developed but also developing countries that were experiencing economic and fiscal crises. It is in the context of adopting NPM that public private partnerships (PPPs) emerged in these economies. This paper attempts to assess the performance of PPPs in Tanzania by using five criteria: relevance, effectiveness, impact, efficiency and sustainability. The assessment shows that except for the cases of efficiency and sustainability, the performance of PPPs has been positive. However, institutional and human capacity of the public sector needs enhancement so that the activities of PPPs are better planned, monitored, and evaluated in order to further improve the performance of PPPs